Trends and Clinical Practice Patterns of Sacral Neuromodulation for Overactive Bladder. Issue 4 (July 2018) - Elterman, Dean S.; Chughtai, Bilal; Vertosick, Emily; Thomas, Dominique; Eastham, James; Sandhu, Jaspreet
Abstract : Objectives: The aim of this study was to investigate surgical practice patterns of American urologists treating refractory overactive bladder (OAB) over the past decade. Refractory OAB remains a management challenge to urologists. When multiple medical therapies have failed, treatment options may include sacral neuromodulation (SNM) or surgery such as augmentation cystoplasty (AC). Methods: Data on SNM and AC performed between 2003 and 2012 by certifying and recertifying urologists were obtained in the form of annualized case logs from the American Board of Urology (ABU). Associations between surgeon characteristics (type of certification, annual volume, practice type, and location) and these procedures were evaluated. Results: Over the past decade, 756 of 6355 urologists certified with the ABU performed SNM or AC for the treatment of refractory OAB. Forty-five (6%) of these surgeons completed fellowships in female urology and 71 surgeons (9%) completed another type of fellowship program. Surgeons recertifying with ABU performed 76% of all SNM procedures. Although SNM and AC have increased from 64 to 2086 between 2003 and 2012, however, this is mainly driven by the increase of SNM from 48 to 2068 cases. Rates of AC have remained stable with 14 to 38 cases reported annually. However, they have declined relative to the total, from 25% in 2003 to less than 1% in 2012. Conclusions: Sacral neuromodulation has increased dramatically over the past decade in surgeons certified with the ABU. This is in contrast to AC, which while remaining stable in number of procedures. Abstract : In comparison with augmentation cystoplasty, sacral neuromodulation has increased over the past decade among surgeons certified with the American Board of Urology.